(untitled) (Rupantaran: A Multidisciplinary Journal, 2025)
The article highlights and discusses the importance of information and communication technology (ICT) in education even though it is theoretical in nature. Similarly, the ICT use in the classroom has significantly changed teaching and learning practices in the twenty-first century. This study examines how ICT tools improve student engagement, skill development, individualized learning, and instructional efficacy in contemporary classrooms. Using recent empirical research and meta-analyses, it illustrates the benefits, challenges, and possible consequences of ICT use in educational settings. Despite the challenges, ICT has a positive impact on education in the twenty-first century’s pedagogical scenario. Additionally, the synthesis demonstrates how ICT promotes digital literacy, clouding in classes, critical thinking, and teamwork, all of which enhance academic performance and prepare students for future digital demands.